Rancang Bangun Sistem Pengolahan Data Gaji Karyawan Berbasis Web - Apriyanto Apriyanto; Nabila Meilianda (REMIK: Riset dan E-Jurnal Manajemen Informatika Komputer, 2025)
The development of computers in the current era has many benefits that we can feel, because of the sophistication of computers in calculating, especially for processing large and difficult data. With data processing programs, the information system will be faster, more precise and accurate. There are still many companies in Indonesia, which still use a manual employee payroll system. And in the financial sector, a system used must be appropriate because in order to avoid recording errors / recapitulating salaries. For this reason, a web-based employee salary data processing information system was created with the aim of providing services in terms of payroll in a company. The method used in designing this system uses the waterfall model, database design uses Entity Relationship Diagrams and logical Records Structure. The navigation structure is also used for the flow of the program process. The programming language uses PHP as a web program, and MySQL as a database application. The design of this information system is the best solution to solve the problems that exist in this company, especially problems in terms of processing employee salary data by utilizing advances in information and communication technology